Impact of Hypothermic Perfusion on Immune Responses and Sterile Inflammation in a Preclinical Model of Pancreatic Transplantation - Benoit Mesnard, MD; Sarah Bruneau, PhD; Stéphanie Le Bas-Bernardet, PhD; Etohan Ogbemudia, MD; Delphine Kervella, MD, PhD; Christophe Masset, MD; Mélanie Neel, PhD; M. David Minault; M. Jeremy Hervouet; Diego Cantarovich, MD, PhD; Jérôme Rigaud, MD, PhD; Lionel Badet, MD, PhD; et al. (Transplantation Direct)
Background. In organ transplantation, cold ischemia is associated with sterile inflammation that subsequently conditions adaptive immunity directed against the grafts during revascularization. This inflammation is responsible for venous thrombosis, which is the main postoperative complication affecting graft function. Our aim was to investigate the modulation of immune responses and endothelial function of pancreatic grafts during cold ischemia using different preservation modalities. Methods. According to a preclinical porcine model of controlled donation after circulatory death, pancreatic grafts were preserved under hypothermic conditions for 24 h according to 4 modalities: static cold storage, hypothermic machine perfusion, hypothermic oxygenated perfusion at 21%, and 100%. Biopsies of the head and tail of the pancreas were performed during preservation. The first step involved a broad screening of the gene expression profile (84 genes) during preservation on a limited number of grafts. In the second step, a confirmation test was performed in all 4 groups. Results. Vascular endothelial growth factor gene expression showed a decrease during preservation in the hypothermic oxygenated perfusion 21% and 100% groups compared with the static cold storage group. In contrast, thrombomodulin gene expression showed an increase during preservation in the hypothermic oxygenated perfusion 21% and 100% groups compared with the static cold storage and hypothermic machine perfusion groups. Conclusions. We demonstrated that compared with static cold storage, hypothermic oxygenated perfusion is an effective modality for modulating endothelial function by increasing thrombomodulin expression and decreasing ischemia and vascular endothelial growth factor expression.